Disparities in Trial of Labor among Women with Twin Gestations in the United States - Mo, Gina N.; Cheng, Yvonne W.; Caughey, Aaron B.; Yee, Lynn M. (American Journal of Perinatology, 2021)
Objective The aim of the study is to examine clinical and demographic factors associated with trial of labor (TOL) among women with twin gestations eligible for a vaginal delivery.Study Design This was a population-based cohort study of women giving birth to twin gestations in the United States (2012–2014). Inclusion criteria for the analysis included live births greater than 23 weeks' gestation and a cephalic presenting twin. Women with prior cesarean delivery were excluded. Women were categorized by whether they underwent a TOL. Clinical and demographic characteristics associated with TOL status were evaluated using multivariable logistic regression analyses. Secondary analyses with stratification by parity and by second twin presentation were performed.Results Of 90,000 women eligible for inclusion, a minority (39.3%) underwent TOL. Women who had a greater gestational age at delivery were more likely to have a TOL. In contrast, several demographic factors were associated with decreased likelihood of TOL, including maternal age >35 years and identifying as Hispanic or Asian compared with non-Hispanic White. No differences in odds of TOL were observed for women who were identified as non-Hispanic Black versus non-Hispanic White, nor were other demographic factors such as marital status, insurance status, or educational attainment associated with undergoing TOL. Clinical factors associated with decreased odds of TOL included nulliparity, obesity, and hypertensive disorders of pregnancy. Results did not substantively change when stratified by parity or second twin presentation, nor did findings differ in the subgroup who delivered at 32 weeks of gestation or greater.Conclusion In this large population of women with twins who were eligible for a TOL, a minority of individuals attempted a vaginal delivery. Demographic and clinical factors such as older maternal age, Asian or Hispanic racial or ethnic identification, nulliparity, and obesity are associated with decreased odds of undergoing TOL.Key Points
Keywords: cesarean delivery; disparities; ethnicity; race; trial of labor; twins